Analisis Karakteristik Elektrik Bentuk Geometri Jalur PCB Menggunakan Pendekatan Finite Element - Maria, Putut Son; Susianti, Elva (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2018)
Some Electronics Computer Aided Design (ECAD) softwares have provided several track shapes to design a Printed Circuit Board (PCB), such as right angle, rounded and trapezoidal. However, it is quite difficult to find scientific literature that can be used as a guide which explains and compiles directly about each character of the geometry. This study aims to analyze and to observe the electrical characteristics of the geometry shape on the Printed Circuit Board (PCB) path by using the finite element method. Each PCB path shape is modeled according to its geometry and physical properties, then calculated for its electrical quantity and be observed for its performance at given current. Simulation and numerical calculations showed that the shape of trapezoidal and rounded geometry have lower resistance and planar inductance of 6.8% and 7.39% respectively than the right angle shape.